Assessment of breeding lines of rice (Oryza sativa L.) carrying the Pi-40 gene for resistance to rice blast strains from Krasnodar region - I. I. Suprun; V. S. Kovalyev; E. S. Kharchenko; E. G. Savenko (Вавиловский журнал генетики и селекции)
Blast caused by fungal pathogen Magnaporthe oryzae B.C. Couch, 2002, is one of the most harmful diseases of rice (Oryza sativa L.), and so the development of resistant varieties is important in rice breeding. Evaluation of the efficiency of blast resistance genes against local populations of the blast pathogen is an important preliminary stage in the formation of the breeding program. In the course of the study, the level of resistance to blast pathogen was estimated for hybrid lines BC1F3 derived from local rice variety Khazar and containing the Pi-40 gene. Plants carrying the dominant allele of the Pi-40 gene in the homozygous state were used in the study. A synthetic population of Magnaporthe oryzae consists of six strains selected at different rice-growing regions in the Krasnodar territory and Rostov region in the season with epiphytotic development of blast disease was used for phytopathological evaluation. Resistance to neck and panicle blast was estimated. Phytopathological testing revealed that the disease had high prevalence in domestic rice varieties Diamant, Courage and Khazar (74.4 %, 57.9 % and 83.3 %, respectively). Khazar/IR 83260-2-10-5-2-1-B hybrid plants from population BC1F3 carrying the target gene showed a high level of resistance (7.6 % prevalence). They are valuable for breeding blast resistant varieties. These findings confirmed a wide spectrum of blast resistance of the Pi-40 gene and promise for use for development of rice cultivars resistant to the population of Magnaporthe oryzae common in the Krasnodar territory.